2021
DOI: 10.1021/acsomega.1c04481
|View full text |Cite
|
Sign up to set email alerts
|

Facile Preparation of β-Cyclodextrin-grafted Chitosan Electrospun Nanofibrous Scaffolds as a Hydrophobic Drug Delivery Vehicle for Tissue Engineering Applications

Abstract: Despite advances in the bio-tissue engineering area, the technical basis to directly load hydrophobic drugs on chitosan (CTS) electrospun nanofibers (ENs) has not yet been fully established. In this study, we fabricated CTS ENs by using an electrospinning (ELSP) system, followed by surface modification using succinyl-beta-cyclodextrin (β-CD) under mild conditions. The β-CD-modified CTS (βCTS) ENs had slightly increased hydrophobicity compared to pristine CTS ENs as well as decreased residual amine content on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The β-cyclodextrin-grafted CS ENFs (β-CD/CS-ENFs) synthesized by Lee et al exploited the surface grafting method. Their report indicated that the graft polymerization method increased the scaffold's thermal stability and hydrophobicity and allowed a sustained release profile [180]. Thus, this method of combining hydrophilic (CS) and hydrophobic components through surface grafting to obtain the ideal adsorption of nutrients and optimal degradation as a drug carrier for hydrophobic drugs might have potential for use in BTE.…”
Section: Graft Polymerizationmentioning
confidence: 99%
“…The β-cyclodextrin-grafted CS ENFs (β-CD/CS-ENFs) synthesized by Lee et al exploited the surface grafting method. Their report indicated that the graft polymerization method increased the scaffold's thermal stability and hydrophobicity and allowed a sustained release profile [180]. Thus, this method of combining hydrophilic (CS) and hydrophobic components through surface grafting to obtain the ideal adsorption of nutrients and optimal degradation as a drug carrier for hydrophobic drugs might have potential for use in BTE.…”
Section: Graft Polymerizationmentioning
confidence: 99%
“…This principle was used for loading chitosan NFs with a hydrophobic drug. Since chitosan NF cannot be loaded with hydrophobic drugs, the amino groups of electrospun chitosan NFs were conjugated with β-cyclodextrin (β-CD) via amide bond without the loss of NF structure or physicochemical properties [ 96 ]. The ability of CD to form inclusion complexes with lipophilic drugs such as dexamethasone resulted in improved drug loading and superior sustained release when compared with unmodified NFs (12 vs. 3 days for complete drug release).…”
Section: Delivery Of Therapeuticsmentioning
confidence: 99%
“…[1][2][3] Due to their structural similarity to the tissue extracellular matrix (ECM) and the large specific surface area, nanofibrous membranes allow the fabrication of multifunctional and tailor-made drug delivery systems for tissue regeneration. 4,5 For instance, Zhu et al fab-ricated an efficient electrospun membrane for wound healing that could guide and promote vascular regeneration via its aligned fibers and by sustained release of the tazarotene drug. 6 However, such a kind of scaffold possesses a twodimensional (2D) structure consisting of tightly packed fiber layers with only superficial pores because, in the electrospinning process, subsequent fiber layers are accumulated one on top of the other.…”
Section: Introductionmentioning
confidence: 99%